Has Indonesia Safeguarded Traditional Cultural Expressions? - Setiyono, Setiyono; Keumala, Dinda; Sabirin, Ahmad; Nursantih, Nadia (Jambura Law Review, 2024)
The Government of the Republic of Indonesia recognized the importance of intellectual property in folklore since the 1982 Copyright Law was enacted (Article 10 of Law No. 6/1982). The study seeks to understand what obstacles Indonesia faces in protecting tribal peoples' communal rights over traditional cultural expressions, also called expressions of folklore in the digital age, and how other nations are resolving them. What is Indonesia's plan for developing and safeguarding traditional cultural manifestations in the digital age, as seen from other nations? The study employs a case-based, normative legal research methodology. The findings, an urgent need for specific institutions that control access benefit sharing from usage by foreign parties, as well as a special anti-theft task force for communal intellectual property rights in the digital era that takes the form of a support organization for tribal peoples. To increase cooperation in the inventorying and documentation of Tribal peoples who own collective intellectual property, optimization also calls for coordination of involvement between the federal government, local governments, and autonomous bodies operating under them, such as the Ministry of Tourism, the Creative Economy Agency, and Tribal peoples' organizations.